Structural basis of histone H3K27 trimethylation by an active polycomb repressive complex 2 - Jiao, Lianying; Liu, Xin (Science (American Association for the Advancement of Science), 2015)
The formation of specialized cell types during development involves the silencing of genes not required in those cell types. An important player in this silencing process is the polycomb repressive complex 2 (PRC2), which methylates histone H3 on lysine residue 27 (H3K27me). Jiao and Liu determined the x-ray crystal structure of a functional PRC2 complex from a thermophilic yeast species (see the Perspective by Schapira). The intimate association of the three subunits confers stability to PRC2. The structure also reveals how the reaction product, H3K27me, stimulates PRC2 allosterically and how a cancer-associated histone mutation blocks the PRC2 active site. Science , this issue p. 10.1126/science.aac4383 ; see also p. 278 The structure of a gene silencing complex reveals how it self-activates and is inhibited by a cancer-associated chromatin mutation. [Also see Perspective by Schapira ] Polycomb repressive complex 2 (PRC2) catalyzes histone H3K27 trimethylation (H3K27me3), a hallmark of gene silencing. Here we report the crystal structures of an active PRC2 complex of 170 kilodaltons from the yeast Chaetomium thermophilum in both basal and stimulated states, which contain Ezh2, Eed, and the VEFS domain of Suz12 and are bound to a cancer-associated inhibiting H3K27M peptide and a S-adenosyl- l -homocysteine cofactor. The stimulated complex also contains an additional stimulating H3K27me3 peptide. Eed is engulfed by a belt-like structure of Ezh2, and Suz12(VEFS) contacts both of these two subunits to confer an unusual split active SET domain for catalysis. Comparison of PRC2 in the basal and stimulated states reveals a mobile Ezh2 motif that responds to stimulation to allosterically regulate the active site.